Mathematical model of the control system of mobile caterpillar robot taking into account kinematic and dynamic parameters - S. A. Pauliukavets; A. A. Velchenko; A. A. Radkevich (Системный анализ и прикладная информатика)
The paper developed a mathematical model of the control system for a mobile tracked robot, which takes into account the kinematic parameters (angular speeds of rotation of the rollers and the center of mass of the robot, the linear speed of the robot and its angle of rotation relative to the normal to the axis) and dynamic parameters (moments of inertia, resistance forces and electromechanical parameters used electric motors), which made it possible to give the most complete mathematical representation of the description of the movement of a caterpillar mobile robot. A control system for mobile robots along a predetermined trajectory is obtained, taking into account position feedback.